2022
DOI: 10.31393/reports-vnmedical-2022-26(3)-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of damage to clothing and external damage to a imitator of the human body using pistols “Fort 12R” AND “AE 790G1”

Abstract: Annotation. The spread of non-lethal firearms among different sections of the population of Ukraine and the increase of their varieties available for sale is another modern challenge for forensic examination. In this regard, there is an urgent need to study the characteristics of injuries caused by the newest types of traumatic guns, taking into account such a factor as clothing. The purpose of the study was to determine the features of the shape and size of damage defects caused by shots from “Fort 12R” and “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
1
Order By: Relevance
“…[10], where numerous correlations of a different nature were also found, both with damage characteristics, parameters of the temporary cavity, and features of the deposition of the residual components of the shot. In particular, in other studies [11], the author and co-authors found convincing evidence regarding the important role of the features of clothing damage in the process of identifying the distance of the shot and the weapon of the shot, which is also quite consistent with the data we obtained.…”
supporting
confidence: 90%
“…[10], where numerous correlations of a different nature were also found, both with damage characteristics, parameters of the temporary cavity, and features of the deposition of the residual components of the shot. In particular, in other studies [11], the author and co-authors found convincing evidence regarding the important role of the features of clothing damage in the process of identifying the distance of the shot and the weapon of the shot, which is also quite consistent with the data we obtained.…”
supporting
confidence: 90%
“…Артродез плечового суглоба -це хірургічне втручання, за якого виконують резекцію суглобових поверхонь гленоїда та головки плечової кістки, фіксують плечову кістку до лопатки з метою формування анкілоза, який у подальшому забезпечує безболісне функціонування верхньої кінцівки в нових функціонально-анатомічних умовах [5,[9][10][11][12]. За даними недавнього системного огляду, 17 досліджень (316 пацієнтів), артродез плечового суглоба допомагає відновити функцію кінцівки, проте має високий ризик ускладнень (33,6 % пацієнтів) -переломи та інфекції [13].…”
Section: вступunclassified